2013
DOI: 10.1002/14651858.cd007662.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy for trichotillomania

Abstract: No particular medication class definitively demonstrates efficacy in the treatment of trichotillomania. Preliminary evidence suggests treatment effects of clomipramine, NAC and olanzapine based on three individual trials, albeit with very small sample sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 56 publications
1
52
0
2
Order By: Relevance
“…In another review of trials assessing the effect of opioid antagonists in behavioural addictions (which included trichotillomania), it was concluded that there is not enough evidence to support the use of opioid antagonists such as naltrexone or nalmefene in trichotillomania [124] . Similarly, there was a Cochrane review published in 2013 which also noted that the literature do not provide strong evidence of a treatment effect for naltrexone in trichotillomania [125] .…”
Section: Discussionmentioning
confidence: 99%
“…In another review of trials assessing the effect of opioid antagonists in behavioural addictions (which included trichotillomania), it was concluded that there is not enough evidence to support the use of opioid antagonists such as naltrexone or nalmefene in trichotillomania [124] . Similarly, there was a Cochrane review published in 2013 which also noted that the literature do not provide strong evidence of a treatment effect for naltrexone in trichotillomania [125] .…”
Section: Discussionmentioning
confidence: 99%
“…Trichotillomania also shares a strong similarity with OCD in terms of underlying abnormalities in corticostriatal pathways as well as some associated impairments in the cognitive abilities linked to the integrity of these brain structures [18,49]. However, in contrast to OCD, trichotillomania is not consistently responsive to serotonin-based pharmacotherapy; it also shows a better response to an non-selective serotonin reuptake inhibitor clomipramine than to SSRIs [50]. Therefore, CBT is typically recommended as the first line of treatment for trichotillomania, especially in children [48].…”
Section: Trichotillomania and Skin Picking Disordermentioning
confidence: 99%
“…Two reviews contained studies with quasiexperimental methods [63,64]. Two reviews in this group did not conduct quantitative synthesis of estimates [61,62], whereas one review meta-analyzed the data for only one outcome, involving two trials [68].…”
Section: Description Of Included Studiesmentioning
confidence: 99%